Interleukin 13 on Microglia is Neurotoxic in Lipopolysaccharide-injected Striatum in vivo - Hong, Ah Reum; Jang, Jae Geun; Chung, Young Cheul; Won, So-Yoon; Jin, Byung Kwan (Experimental neurobiology, 2022)
To explore the potential function of interleukin-13 (IL-13), lipopolysaccharide (LPS) or PBS as a control was unilaterally microinjected into striatum of rat brain. Seven days after LPS injection, there was a significant loss of neurons and microglial activation in the striatum, visualized by immunohistochemical staining against neuronal nuclei (NeuN) and the OX-42 (complement receptor type 3, CR3), respectively. In parallel, IL-13 immunoreactivity was increased as early as 3 days and sustained up to 7 days post LPS injection, compared to PBS-injected control and detected exclusively within microglia. Moreover, GFAP immunostaining and blood brain barrier (BBB) permeability evaluation showed the loss of astrocytes and disruption of BBB, respectively. By contrast, treatment with IL-13 neutralizing antibody (IL-13NA) protects NeuN neurons against LPS-induced neurotoxicity . Accompanying neuroprotection, IL-13NA reduced loss of GFAP astrocytes and damage of BBB in LPS-injected striatum. Intriguingly, treatment with IL-13NA produced neurotrophic factors (NTFs) on survived astrocytes in LPS-injected rat striatum. Taken together, the present study suggests that LPS induces expression of IL-13 on microglia, which contributes to neurodegeneration via damage on astrocytes and BBB disruption in the striatum .